Technology Of Enchanment From Zapin Pecah Dua Belas Dance Method Based On Locality Values - Nike Suryani; M. Jazulli; Agus Cahyono; M. Ibnan Syarif (International Conference on Science, Education, and Technology, 2022)
The Zapin Pecah Dua Belas dance is a traditional dance from the Pelalawan area. It's called the pecah dua belas dance because it has twelve varietie, Zapin dance developed well in the Pelalawan area, this dance is used as a mandatory material in the Bina Tasik Studio that must be mastered by every student. The purpose of the study was to analyze the learning process of the Zapin Pecah Dua Belas dance based on local wisdom values. This study uses a qualitative method to explore the charm that is built up in the learning process of the Zapin Pecah Dua Belas Dance. Data collection techniques were carried out through interviews, observation and documentation. Research result ; echantment in the Pecah Dua Belas Dance is seen from the variety of Zapin dances, the complete learning process begins with the provision of material on hands, body postures and feet. The findings in this study show that there is a charm that is built from the zapin dance learning process based on local values.